Conclusion and Future Recommendation - Jia-Rey Chang (A+BE: Architecture and the Built Environment)
Interactive Architecture should embody the features of “Information”, “Improvisation”, and “Integration” in order to generate sufficient “Intelligence” to embody the authentic kernel of “Organic Architecture”.